2021
DOI: 10.1016/j.jbc.2021.101418
|View full text |Cite
|
Sign up to set email alerts
|

The mGluR6 ligand-binding domain, but not the C-terminal domain, is required for synaptic localization in retinal ON-bipolar cells

Abstract: Signals from retinal photoreceptors are processed in two parallel channels—the ON channel responds to light increments, while the OFF channel responds to light decrements. The ON pathway is mediated by ON type bipolar cells (BCs), which receive glutamatergic synaptic input from photoreceptors via a G-protein-coupled receptor signaling cascade. The metabotropic glutamate receptor mGluR6 is located at the dendritic tips of all ON-BCs and is required for synaptic transmission. Thus, it is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 66 publications
(120 reference statements)
1
15
0
Order By: Relevance
“…7 ). WT mGluR6-EGFP exhibited normal dendritic tip localization, as we reported previously ( 18 , 32 ). All single mutants were capable of enrichment in TRPM1-containing puncta in the OPL ( Fig.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…7 ). WT mGluR6-EGFP exhibited normal dendritic tip localization, as we reported previously ( 18 , 32 ). All single mutants were capable of enrichment in TRPM1-containing puncta in the OPL ( Fig.…”
Section: Resultssupporting
confidence: 86%
“…The predicted molecular mass of the mGluR6 precursor protein is ∼95 kDa and that of the mature protein after cleavage of the N-terminal signal peptide is ∼92 kDa. In SDS-PAGE, mGluR6 from rodent retina tissue migrates as a presumptive dimer of ∼200 kDa ( 2 , 18 , 23 , 24 ). We observed that mouse mGluR6 expressed in HEK cells by transient transfection migrated as a doublet near the expected dimer size.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations